PENGARUH WAKTU PENYIMPANAN DARAH TERHADAP KADAR HEMOGLOBIN PADA KOMPONEN WHOLE BLOOD DARAH DONOR - Arief Adi Saputro; Catur Retno Lestari (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Blood transfusion is the process of distributing blood from donors to patients with the aim of replacing blood lost due to bleeding, surgery, shock and malfunctioning of the blood-forming organs that require replacement blood in the form of whole blood or blood components. Blood is stored with the First in First Out (FIFO) system, which is a system that regulates the expulsion of blood in which the first blood that enters will be removed first. The storage period of blood will experience changes in blood components, especially erythrocytes will experience significant changes in shape over the length of time blood storage. The purpose of this study was to determine the difference in hemoglobin levels of donor blood before and after storage for 7 days. This research was conducted at the Blood Transfusion Unit of PMI Kudus Regency. The number of samples used as many as 15 samples. The results showed that there were differences in hemoglobin levels before storage and after storage for 7 days (0.000). The average value before storage was 14.7 g/dl, after storage for 7 days 18.2 g/dl, the highest hemoglobin before storage was 15.4 g/dl, the highest after storage was 18.2 g/dl, while the lowest hemoglobin was before storage. storage 14.0 gr/dl and after storage 17.3 gr/dl. The conclusion is there is a significant difference between hemoglobin levels before storage and after storage for 7 days.